DAMPAK ROTASI TANAM TERHADAP PERSPEKTIF EKONOMI PETANI HORTIKULTURA DI KECAMATAN LANDONO KABUPATEN KONAWE SELATAN DENGAN PENDEKATAN KUALITATIF - Nurmaya; Hajar; Rosmalah, Sitti; Maulid Sari, Awal (Jurnal Pertanian Agros, 2025)
This study aims to analyze the impact of crop rotation on the economic perspective of horticulture farmers in Landono District, South Konawe Regency, using a qualitative approach. In horticulture farming, cost efficiency and income optimization are key to success. Although quantitative data from three farmers (Nanang, Yohan, and Suparti) show differences in financial performance, a deep understanding of how farmers perceive and manage crop rotation practices and their impact on their economic condition still needs to be explored. Through in-depth interviews, this study explores farmers' understanding of crop rotation concepts, the practices they undertake, and their perceptions of its influence on farming costs, income, and profits. Initial findings suggest that farmers who intensively apply crop rotation tend to have a more positive view of their farming efficiency, although this is not always directly proportional to the highest absolute profit. This study concludes that farmers' understanding of crop rotation as an economic efficiency strategy needs to be strengthened through appropriate counseling and policy support.